PERANCANGAN PEREDUP LAMPU FLUORESCENT DENGAN SAKLAR PEMULIH ENERGI MAGNETIK - , Margono ,ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Power regulator for fluorescent lamp can be controlled by adjusting the voltage source to get satisfying light. The objective of this research is to obtain MERS characteristics as dimming device and fluorescent lamp controller. The Method is to design fluorescent light dimmer using MERS. PSIM software was used to simulate the design. The simulation result used to make prototype and tested. To obtain the proper and unproper criterions of this MERS device are represented by smaller capacitancy than resonance, capacitor maximum voltage twice than its source and have low harmonic effect. The simulation shows MERS can improve power factor to 0,53 with harmonic distortions THDi = 22,4 %, THDv = 2,95 % and regulator electric power consumption to 12 %.